Analysis of Service Quality, Entrepreneurial Marketing, and Intellectual Capital to increasing SME’s Performance - Siregar, Muhammad Yamin; Rafiki, Ahmad; Hidayat, Nasrullah (Jurnal Manajemen Pelayanan Publik, 2024)
This study aims to analyze and prove empirically how to improve the SME's performance and sustainable competitive advantage in North Sumatera through Entrepreneurial Marketing, Intellectual Capital, Service Quality, and Innovation Capability as intervening variables. The research population consists of all 84,758 SMEs. Determining the samples in this research uses purposive sampling: a data source sampling technique with certain considerations. The sample size was 218 leading SME samples, from eight leading SME product categories: foods and beverages, handicrafts, fashion, agribusiness, bakeries, restaurants, services, and coffee shops. Data analysis uses Smart PLS. The results of this research show Intellectual Capital has a positive and significant effect on Innovation Capability; Service Quality has a positive and significant impact on Innovation Capability; Intellectual Capital has a positive and significant effect on SME Performance; Service Quality has a positive and significant impact on SME Performance; Entrepreneurial Marketing has a positive and significant effect on Innovation Capability and SME Performance; Innovation Capability positively and significantly mediates the relationship between Intellectual Capital and SME Performance; Service Quality with SME Performance; Entrepreneurial Marketing with SME Performance.